Penetrating Aortic Injury due to Broken Ribs and Preventive Measures - Yanagawa, Youichi; Nagasawa, Hiroki; Ishikawa, Kouhei; Hirayama, Shunki; Itoi, Akira; Mogami, Atsuhiko (AORTA, 2022)
We herein report two cases of patients that underwent prophylactic operations to prevent aortic injuries in association with fractured ribs. Penetrating aortic injuries induced by fractured ribs remain fatal. Prophylactic operations appear effective. However, the indication for such operations should be clarified further in the future.
Keywords: fractured rib; penetrating aortic injury; operation